Penguatan Pendidikan Agama Khonghucu di Indonesia: Kebijakan Tata Kelola SeTiAKIN Bangka Belitung - Wahyudi, Firman (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article analyzes standar of the State Confucian Religious College of Indonesia (SeTiAKIN) Bangka Belitung. It posits that optimizing governance is a crucial prerequisite for strengthening Confucian religious education in Indonesia. The primary issues identified are the sub-optimal institutional governance resulting from the absence or incompleteness of internal regulations and Standard Operating Procedures, the availability of qualified human resources (HR), including both lecturers and educational staff, and the lack of mechanisms for regular regulatory review and updates. This situation directly impacts the hindered standardization of educational quality and the limited availability of professional and integral educators and religious counselors.Using a qualitative case study approach, this article explores how these regulatory gaps and weaknesses impede SeTiAKIN's strategic role as a center for Confucian education. The findings indicate that without having robust and adaptive governance framework, the institution struggles to achieve the principles of Good University Governance and fulfill its national policy mandate. Therefore, to address these fundamental problems, this policy article recommends a Minister of Religious Affairs Regulation on General Guidelines for Transparent, Participative, and Accountable Governance of State Religious Higher Education Institutions.